2019
DOI: 10.1016/j.red.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and inequality in a monetary Schumpeterian model with heterogeneous households and firms

Abstract: This study develops a Schumpeterian growth model with heterogeneous households and heterogeneous …rms to explore the e¤ects of monetary policy on innovation and income inequality. Household heterogeneity arises from an unequal distribution of wealth. Firm heterogeneity arises from random quality improvements and a cost of entry. We …nd that under endogenous …rm entry, in ‡ation has inverted-U e¤ects on economic growth and income inequality. We also calibrate the model for a quantitative analysis and …nd that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…However, there is no consensus on the effect of inflation on income inequality. For example, Chu et al (2019) demonstrated the existence of an inverted-U-shape relationship between inflation and income inequality. However, Zheng…”
Section: Empirical Modelmentioning
confidence: 99%
“…However, there is no consensus on the effect of inflation on income inequality. For example, Chu et al (2019) demonstrated the existence of an inverted-U-shape relationship between inflation and income inequality. However, Zheng…”
Section: Empirical Modelmentioning
confidence: 99%
“…Finally, using (12) to replace w t l x,t and substituting 13, (14), and (16) into the previous equation to replace (1 + βi) w t l r,t , we get…”
Section: Labor Market and The Final Goods Market Clearing Conditionmentioning
confidence: 99%
“…It is worth noting that Sidrauski (1967) proves the superneutrality of money in a qualitatively equivalent approach which assumes money enters the utility function. 12 As explained by Sidrauski (1967, p. 544), "In the short run, an increase in the rate of monetary expansion is equivalent to a rise in government transfers to the private sector. It therefore results in an increase in consumption and a fall in the rate of capital accumulation."…”
Section: Comparison With a Monetary Ak Model With The Socmentioning
confidence: 99%
“…While all of these early studies feature full employment, some subsequent studies use different approaches to incorporate equilibrium unemployment into the R&D‐based growth model 2 . A branch of this literature uses variants of the R&D‐based growth model to explore the effects of minimum wage on unemployment and innovation; see Askenazy (2003), Meckl (2004), Agenor and Lim (2018), Chu et al (2020), and Chu, Kou, and Wang (2020). This study contributes to this literature by showing that minimum wage has heterogeneous effects on innovation of different firms, and by testing these heterogeneous effects using firm‐level data.…”
Section: Introductionmentioning
confidence: 99%